Noise and Electrical Oscillations Generation during the Investigation of the Resistive Switching in the Yttria Stabilized Zirconia Films by Conductive Atomic Force Microscopy. (29th October 2015) - Gorshkov, Oleg; Filatov, Dmitry; Antonov, Dmitry; Antonov, Ivan
Abstract : The effect of resistive switching in the yttria stabilized zirconia (YSZ) thin films on Si substrates has been studied by Conductive Atomic Force Microscopy (CAFM). The resistive switching of the YSZ films from the low conductive state to the highly conductive one has been found to be associated with the increasing of the noise with broad frequency spectrum related to the redistribution of the oxygen vacancies in YSZ. The electrical oscillations in oscillation loop connected in series to the CAFM probe, the sample, and the bias source related to the excitation of the oscillation loop by the noise in the probe-to-sample contact film have been observed. The effect discovered is promising for application in the memristor devices of new generation.